Pengaruh Transparansi Akuntabilitas Dan Partisipasi Masyarakat Terhadap Pengelolaan Keuangan Desa - Andika Subandra; Usdeldi; Eri Nofriza (Journal of Applied Accounting And Business, 2022)
Village financial management is an overall activity that includes planning, implementation, administration, reporting, and accountability for village funds. This study aims to determine the effect of transparency, accountability, and community participation on village financial management. The sample of this research is the entire community in Pebenaan Village, Keritang District, Indragiri Hilir Regency. This type of research is descriptive quantitative research. The sampling method used purposive sampling, namely random sampling based on certain criteria for each member of the population to be a sample so as to produce 98 respondents. The data was obtained by distributing questionnaires to the residents of Pebenaan Village. Hypothesis testing in this study uses Multiple Linear Regression Analysis, Classical Assumption Test, and Hypothesis Testing with SPSS version 21 tool. The results show that Transparency has no effect on Village Financial Management, Accountability and Community Participation affect Village Financial Management. Based on the results of the Coefficient of Determination, it is found that Transparency, Accountability and Community Participation simultaneously affect village financial management with a value of 75.50%, while the other 24.50% are influenced by other variables outside of this study.